Cellulose acetate tow with low DPF and low titanium dioxide content
Through ashing and titanium particle counting density measurement, cellulose acetate tows with low titanium dioxide content are produced, which solves the problems of production difficulties and insufficient analysis methods, and achieves efficient and accurate production and measurement results.
Patent Information
- Application Number
- CN202080060183.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-08-27
- Filing Date
- 2020-04-17
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2040-04-17
AI Technical Summary
The prior art faces manufacturing difficulties in producing cellulose acetate tows with low titanium dioxide content, including maintaining low titanium dioxide content, producing tows of a certain color, and producing tows of a consistent color. At the same time, conventional analysis methods are insufficient, making it difficult to accurately measure low concentrations of titanium dioxide and color.
Cellulose acetate tows with less than 0.1 wt.% titanium dioxide were prepared by ashing and titanium particle counting density measurements. At the same time, a method for measuring the titanium dioxide content of cellulose acetate was developed, including preparing samples, ashing, dissolving, titrating blank solutions with titanium standards, and comparing the titrated blank solutions with sample solutions.
Improved yarn breaking resistance of cellulose acetate tows, reduced production costs, met consumers' demand for more natural products, and provided a method for accurately and accurately measuring the titanium dioxide concentration and color of cellulose acetate tows.
Smart Images

Figure CN114364271B_ABST
Abstract
Description
[0001] Priority claim
[0002] This application claims the benefit of U.S. Application No. 62 / 892,297, filed on August 27, 2019, the entire disclosure of which is incorporated herein by reference in its entirety for all purposes. Technical Field
[0003] The present disclosure generally relates to cellulose acetate tow having low titanium dioxide content. Specifically, the present disclosure relates to cellulose acetate tow bands having less than 0.1 wt.% titanium dioxide. The present disclosure also relates to methods for preparing and analyzing cellulose acetate tow having low titanium dioxide content. Background Art
[0004] Cellulose esters such as cellulose acetate are known for their robust uses, particularly as filaments and fibers. Indeed, cellulose acetate is one of the major types of natural-based fibers and has many commercial applications. For example, cellulose acetate tow is commonly used to make cigarette filters. During conventional tow manufacturing, a matting agent, typically titanium dioxide, is incorporated at various processing steps to provide a specific opacity to the final cigarette filter. The addition of titanium dioxide during conventional cellulose acetate tow manufacturing can also ensure uniformity in the appearance of the tow. Titanium dioxide can also be used to accelerate the photodegradation of cigarette filters, which is an important consideration in minimizing the waste problem associated with discarding waste cigarettes.
[0005] Although titanium dioxide is a common additive in cellulose acetate tow, the present inventors have discovered that the addition of titanium dioxide may have a negative or other detrimental effect on the manufacture of cellulose acetate tow and on the cellulose acetate tow itself. Titanium dioxide additives are typically purchased separately and therefore increase the overall cost of manufacturing cellulose acetate tow. Therefore, removing or omitting titanium dioxide can reduce manufacturing costs.
[0006] By removing or omitting titanium dioxide, wear on manufacturing machinery may also be reduced. For example, the present inventors have discovered that the presence of titanium dioxide in cellulose acetate tow may cause wear on crimping machines or other machinery.
[0007] In summary, the present inventors have discovered that reducing or omitting titanium dioxide improves both qualities. For example, studies have shown that the presence of titanium dioxide can cause yarn breakage during the spinning process of cellulose acetate fibers. Yarn or thread breakage during the spinning process reduces production efficiency. These studies show that by reducing the titanium dioxide content and / or omitting titanium dioxide in the cellulose acetate tow during production, yarn breakage can be prevented and production efficiency can be improved.
[0008] In addition, consumers may prefer products containing cellulose acetate fibers that do not contain titanium dioxide. The present inventors have found that consumers often perceive added titanium dioxide as an impurity in the product. This may be undesirable for consumers who prefer more "natural" or "organic" products.
[0009] Therefore, there is a need for cellulose acetate tow having a low titanium dioxide content.
[0010] The present inventors have discovered, however, that attempts to produce cellulose acetate tow having a low titanium dioxide content have been hampered by a number of manufacturing difficulties, including the difficulty of ensuring a consistently low titanium dioxide content, the difficulty of producing cellulose acetate tow of a certain color, and the difficulty of producing cellulose acetate tow of a consistent color.
[0011] Furthermore, the present inventors have discovered that the production of cellulose acetate tow having a low titanium dioxide content is not feasible due to inadequate methods of analytical measurement and / or quality control. For example, the present inventors have discovered that conventional methods of measuring the titanium dioxide content of cellulose acetate tow are unable to accurately measure low concentrations of titanium dioxide. Similarly, conventional methods of measuring the color of cellulose acetate tow are unable to accurately measure the color of cellulose acetate tow having a low titanium dioxide content.
[0012] Therefore, there is also a need for new analytical methods applicable to cellulose acetate tow having a low titanium dioxide content. Summary of the invention
[0013] In some embodiments, the present disclosure relates to a tow band comprising cellulose acetate fibers; wherein the tow band comprises less than 0.1 wt.% titanium dioxide as measured by ashing and / or titanium particle count density; and wherein the tow band has an "L" value from 90 to 100, an "a" value from -1 to -0.5, and / or a "b" value from 3 to 6 as measured from a spinning solution solution. In some aspects, the tow band comprises less than 0.01 wt.% titanium dioxide. In some aspects, the tow band has an ash weight of less than 0.1% of the tow band. In some aspects, the tow band has less than 1.0 titanium dioxide particles / denier. In some aspects, the tow band has less than 12.5 single filament denier. In some aspects, the tow band has a total denier from 5,000 to 100,000. In some aspects, the cellulose acetate fibers have a cross-sectional shape selected from the group consisting of: circular, generally circular, crenulated, mortise, generally mortise, polygonal, generally polygonal, dog-bone, "Y", "X", "K", "C", multi-lobal, and any combination thereof.
[0014] In some embodiments, the present disclosure also relates to a method for measuring the titanium dioxide content of cellulose acetate, the method comprising: preparing a sample of cellulose acetate for measurement; ashing the sample to form an ashed sample; dissolving the ashed sample to form a sample solution; titrating a blank solution with a titanium standard; and comparing the titrated blank solution with the sample solution. In some aspects, the titanium dioxide content of cellulose acetate is less than 1000 ppm. In some aspects, the titanium dioxide content of cellulose acetate is 15 ppm or more. In some aspects, the preparation comprises treating cellulose acetate with an organic non-solvent, the organic non-solvent being selected from the group consisting of isopropanol, diethyl ether, 2-butanol, methyl tert-butyl ether, isopropyl ether, 2-pentanone, isobutyl acetate, ethylene glycol methyl ether, alcohol, ether, ketone, ester, or other non-solvent and combinations thereof. In some aspects, ashing further comprises: burning the sample; and treating with a salt, the salt being selected from the group consisting of sodium pyrosulfate, sodium sulfate, sodium bisulfate, potassium pyrosulfate, potassium bisulfate, potassium sulfate, potassium bisulfate, and combinations thereof. In some aspects, dissolving comprises dissolving the ashed sample in water and / or acid. In some aspects, the method further comprises treating the sample solution with hydrogen peroxide. In some aspects, the blank solution comprises water, sulfuric acid and hydrogen peroxide. In some aspects, the titanium standard comprises from 0.1 to 50 ppm titanium dioxide.
[0015] In some embodiments, the disclosure also relates to a method for measuring the color of a spinning solution solution of cellulose acetate, the method comprising: preparing a cake of cellulose acetate from the spinning solution solution; providing a tile; placing the cake and the tile on a reflective port of a colorimeter so that the tile is behind the cake; and recording the color of the cake using the colorimeter. In some aspects, the preparation comprises pressing the cellulose acetate on a hot plate. In some aspects, the tile is white.
[0016] In some embodiments, the present disclosure is also directed to a tow band comprising: cellulose acetate fibers having a per filament denier of less than 12.5 and a total denier of from 5,000 to 100,000; and wherein the tow band is substantially free of titanium dioxide.
[0017] In some embodiments, the present disclosure also relates to a tow band comprising: cellulose acetate fibers having a single filament denier of less than 12.5; wherein the tow band comprises less than 0.1 wt. % titanium dioxide, and wherein the tow band has an average titanium dioxide particle density of less than 1.0 titanium dioxide particles / fiber denier. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] The present disclosure is described in detail below with reference to the drawings, wherein like numerals represent like parts.
[0019] FIG. 1A shows a cross-sectional image analysis of conventional cellulose acetate fibers.
[0020] Figure 1B Shown is a cross-sectional image analysis of cellulose acetate fibers according to an embodiment of the present disclosure. DETAILED DESCRIPTION
[0021] introduction
[0022] The present disclosure relates to a tow band comprising cellulose acetate fibers, wherein the tow band comprises less than 0.1 wt.% titanium dioxide, and wherein the content of titanium dioxide in the tow band is measured by ashing and / or titanium particle count density. The present disclosure further relates to a method of measuring the titanium dioxide content of cellulose acetate tow. The present disclosure also relates to a method for measuring the color of cellulose acetate tow.
[0023] Advantageously, the tow bands disclosed herein exhibit improved resistance to yarn breakage while also being more cost-effective to produce and meeting consumer demand for more natural products. Furthermore, the methods disclosed herein advantageously allow for accurate and precise measurement of titanium dioxide concentration and color, respectively, of cellulose acetate tow. These methods are advantageously applicable to measuring tow bands having low titanium dioxide content, such as those tow bands according to embodiments disclosed herein.
[0024] Cellulose acetate
[0025] As described herein, the present disclosure is directed to a tow band of cellulose acetate fibers, wherein the tow band comprises less than 0.1 wt. % titanium dioxide.
[0026] Cellulose acetate can be prepared by known methods, including those disclosed in US Pat. No. 2,740,775 and US Publication No. 2013 / 0096297, the entire contents of which are incorporated herein by reference. Typically, acetylated cellulose is prepared by reacting cellulose with an acetylating agent in the presence of a suitable acidic catalyst and then deesterifying.
[0027] Cellulose can come from a variety of materials, including cotton linters, softwood, or hardwood. Softwood is a general term typically used to refer to wood from conifers (i.e., conifers from the order Pinus piniformes). Trees that produce softwood include pine, spruce, cedar, fir, larch, Douglas fir, hemlock, cypress, redwood, and yew. In contrast, the term hardwood is typically used to refer to wood from broadleaf or angiosperm trees. The terms "softwood" and "hardwood" do not necessarily describe the actual hardness of the wood. However, on average, the density and hardness of hardwood are higher than those of softwood, but there is considerable variation in the actual hardness of the two groups of wood, and some softwood trees can actually produce wood that is harder than that from hardwood trees. One feature that distinguishes hardwood from softwood is the presence of pores or vessels in hardwood trees, which are absent in softwood trees. At a microscopic level, softwood contains two types of cells, i.e., longitudinal wood fibers (or tracheids) and transverse ray cells. In softwood, water transport within the tree is through tracheids rather than pores in hardwood. In some aspects, hardwood cellulose is preferred for acetylation.
[0028] Acylating agent can comprise carboxylic acid anhydride (or simply acid anhydride) and carboxylic acid halide, particularly carboxylic acid chloride (or simply acid chloride).Suitable acid chloride can comprise, for example, acetyl chloride, propionyl chloride, butyryl chloride, benzoyl chloride and similar acid chloride.Suitable acid anhydride can comprise, for example, acetic anhydride, propionic anhydride, butyric anhydride, benzoic anhydride and similar acid anhydride.Also can use the mixture of these acid anhydrides or other acylating agents, so that different acyl groups are introduced into cellulose.In certain embodiments, mixed acid anhydride, for example acetic propionic anhydride, acetic butyric anhydride etc. also can be used for this purpose.
[0029] In most cases, cellulose is thoroughly acetylated with an acetylating agent to produce a derivatized cellulose having a high degree of substitution (DS) value (e.g., from 2.4 to 3), and in some cases some additional hydroxyl substitution (e.g., sulfate). Exhaustively acetylation of cellulose refers to an acetylation reaction that is driven toward completion such that as many hydroxyl groups as possible in the cellulose undergo the acetylation reaction.
[0030] Suitable acidic catalysts for promoting the acetylation of cellulose usually contain a mixture of sulfuric acid or sulfuric acid and at least one other acid. Other acidic catalysts that do not contain sulfuric acid can be used to promote acetylation similarly. In the case of sulfuric acid, at least some of the hydroxyl groups in the cellulose can become initially functionalized as sulfates during the acetylation reaction. Once thoroughly acetylated, cellulose is subjected to a controlled partial deesterification step (usually in the presence of a deesterifying agent), which is also referred to as a controlled partial hydrolysis step.
[0031] As used herein, deesterification refers to a chemical reaction during which one or more ester groups of the intermediate cellulose ester are cleaved from cellulose acetate and replaced with hydroxyl groups, resulting in a cellulose acetate product having a (second) DS of less than 3. As used herein, "deesterifying agent" refers to a chemical reagent capable of reacting with one or more ester groups of cellulose acetate to form hydroxyl groups on the intermediate cellulose ester. Suitable deesterifying agents include low molecular weight alcohols such as methanol, ethanol, isopropanol, amyl alcohol, R-OH (wherein R is C1 to C1 20 alkyl), and mixtures thereof. Water and mixtures of water and methanol may also be used as deesterifying agents. Typically, most of these sulfates break in a controlled partial hydrolysis process for reducing the amount of acetyl substitution. The reduced degree of substitution may be in the range of from 0.5 to 2.9, for example from 1.5 to 2.9 or from 2 to 2.6. The degree of substitution may be selected based on at least one organic solvent used in the adhesive composition. For example, when acetone is used as the organic solvent, the degree of substitution may be in the range of from 2.2 to 2.65.
[0032] The number average molecular weight of cellulose acetate can be from 30,000amu to 100,000amn, for example, from 50,000amu to 80,000amn, and can have a polydispersity from 1.5 to 2.5, for example, from 1.75 to 2.25 or from 1.8 to 2.2. Unless otherwise stated, all molecular weights described herein are number average molecular weights. The molecular weight can be selected based on the desired hardness of the final tow or filter rod. Although a larger molecular weight leads to increased hardness, a larger molecular weight also increases viscosity. Cellulose acetate can be provided in powder or flake form.
[0033] In some aspects, blends of cellulose acetate flakes or powders of different molecular weights can be used. Thus, a blend of high molecular weight cellulose acetate (e.g., cellulose acetate having a molecular weight greater than 60,000 amu) can be blended with low molecular weight cellulose acetate (e.g., cellulose acetate having a molecular weight less than 60,000 amu). The ratio of high molecular weight cellulose acetate to low molecular weight cellulose acetate can vary, but generally can be in the range of from 1:10 to 10:1; for example, from 1:5 to 5:1 or from 1:3 to 3:1.
[0034] Cellulose acetate fibers, tow and tow packages
[0035] There are many methods for forming fibers from cellulose esters, which can be used to form cellulose acetate fibers of the present disclosure. In some embodiments, in order to form fibers from cellulose esters, a spinning solution is formed by dissolving the cellulose ester in a solvent to form a spinning solution solution. The spinning solution solution is typically a high viscosity solution. The solvent of the spinning solution solution can be selected from the group consisting of: water, acetone, methyl ethyl ketone, methylene chloride, dioxane, dimethylformamide, methanol, ethanol, glacial acetic acid, supercritical carbon dioxide, any suitable solvent capable of dissolving the above-mentioned polymers, and combinations thereof. In some aspects, the solvent is acetone or a combination of acetone and up to 5wt.% water. Pigments can also be added to the spinning solution. The spinning solution can contain, for example, cellulose acetate from 10 to 40wt.% and solvent from 60 to 90wt.%. Pigment, when added, can be with from 0.1 to 5wt.%, for example, from 0.1 to 4wt.%, from 0.1 to 3wt.%, from 0.1 to 2wt.%, from 0.5 to 5wt.%, from 0.5 to 4wt.%, from 0.5 to 3wt.%, from 0.5 to 2wt.%, from 1 to 5wt.%, from 1 to 4wt.%, from 1 to 3wt.% or from 1 to 2wt.% exist.Then, before spinning to form fiber, spinning solution is filtered and degassed.Spinning solution can be spun in a spinning machine comprising one or more chambers, and each chamber comprises a spinneret.Spinneret comprises the hole that affects the speed that solvent evaporates from fiber.
[0036] The pigment added to the spinning solution is not particularly limited, and any conventional pigment may be used. Examples of common, suitable pigments include calcium carbonate, diatomaceous earth, magnesium oxide, zinc oxide, and barium sulfate.
[0037] Generally speaking, the production of tow band packages may involve spinning fibers from a spinning solution, forming tow bands from the fibers, crimping the tow bands, and packaging the crimped tow bands. In the production, optional steps may include, but are not limited to, heating the fibers after spinning, applying a finish or additive to the fibers and / or tow bands before crimping, and conditioning the crimped tow bands. The parameters of at least these steps are important for producing the desired package.
[0038] It should be noted that the size and shape of the bag can vary depending on the needs of further processing. In some embodiments, the bag can have dimensions ranging from 30 inches (76 cm) to 60 inches (152 cm) in height, 46 inches (117 cm) to 56 inches (142 cm) in length, and 35 inches (89 cm) to 45 inches (114 cm) in width. In some embodiments, the weight of the bag can range from 900 pounds (408 kg) to 2100 pounds (953 kg). In some embodiments, the bag can have a mass greater than 300 kg / m 3 (18.8lb / ft3 ) density.
[0039] fiber
[0040] In some embodiments, the tow band has less than 12.5 dpf, for example, less than 12 dpf, less than 10 dpf, less than 8 dpf, or less than 6 dpf. In these embodiments, the tow band can have greater than 1 dpf, for example, greater than 2 dpf, greater than 3 dpf, greater than 4 dpf, or greater than 15 dpf. In terms of range, the filament bands of these embodiments can have from 1 to 12.5 dpf, for example, from 1 to 12 dpf, from 1 to 10 dpf, from 1 to 8 dpf, from 1 to 6 dpf, from 2 to 12.5 dpf, from 2 to 12 dpf, from 2 to 10 dpf, from 2 to 8 dpf, from 2 to 6 dpf, from 3 to 12.5 dpf, from 3 to 12 dpf, from 3 to 10 dpf, from 3 to 8 dpf, from 3 to 6 dpf, from 4 to 12.5 dpf, from 4 to 12 dpf, from 4 to 10 dpf, from 4 to 8 dpf, or from 4 to 6 dpf.
[0041] Fibers for use in the present disclosure may have any suitable cross-sectional shape, including, but not limited to, circular, generally circular, crenulated, mortise, generally mortise, polygonal, generally polygonal, dog-bone, "Y", "X", "K", "C", multi-lobal, and any mixture thereof. As used herein, the term "multi-lobal" refers to a cross-sectional shape having a point (not necessarily at the center of the cross-section) from which at least two lobes extend (not necessarily evenly spaced or evenly sized).
[0042] As described above, the fibers used in the present disclosure can be produced by any method known to those skilled in the art. As described, in some embodiments, the fibers can be produced by spinning a spinning solution through a spinneret. As used herein, the term "spinning solution" refers to a cellulose acetate solution and / or suspension from which fibers are produced. In some embodiments, the spinning solution may contain cellulose acetate and a solvent. In some embodiments, the spinning solution used in conjunction with the present disclosure may contain cellulose acetate, a solvent, and an additive. In some embodiments, the concentration of cellulose acetate in the spinning solution may range from 10 to 40 wt.% (e.g., from 20 to 30 wt.%, from 25 to 40 wt.%, from 25 to 30 wt.%), and the concentration of the solvent may range from 60 to 90 wt.% (e.g., 60 to 80 wt.%, 70 to 80 wt.%, 80 to 90 wt.%). In some embodiments, the spinning dope may be heated to a temperature ranging from 40°C to 100°C (eg, from 45°C to 95°C, from 50°C to 90°C, from 55°C to 85°C, from 60°C to 80°C).
[0043] Suitable solvents may include, but are not limited to, water, acetone, methyl ethyl ketone, methylene chloride, dioxane, dimethylformamide, methanol, ethanol, glacial acetic acid, supercritical CO2, any suitable solvent capable of dissolving the above-mentioned polymer, or any combination thereof. As a non-limiting example, the solvent for cellulose acetate may be an acetone / methanol mixture. In certain embodiments, in order to produce the very high dpf value of the present disclosure, the solvent level increased compared to the amount of typical dpf values (e.g., 2 to 8 dpf) may be used. For example, in certain embodiments, in order to produce the tow of very high dpf, the amount of solvent may be high from 5 to 30wt.% when compared to the amount of solvent of typical dpf tow. In some cases, the additional amount of solvent may bring challenges to the processing of fiber.
[0044] Some embodiments of the present disclosure may involve treating fibers to achieve surface functionality on the fibers. In some embodiments, the fibers may include surface functionality including, but not limited to, biodegradable sites (e.g., defect sites that increase surface area to improve biodegradability), chemical treatments (e.g., carboxylic acid groups for subsequent functionalization), active particle binding sites (e.g., sulfide sites for binding gold particles or chelating groups for binding iron oxide particles), sulfur moieties, or any combination thereof. One skilled in the art will appreciate the various methods and mechanisms for achieving surface functionality. Some embodiments may involve impregnation, spraying, ionization, functionalization, acidification, hydrolysis, exposure to plasma, exposure to ionized gases, or any combination thereof to achieve surface functionality. Suitable chemicals for imparting surface functionality may be any chemical or collection of chemicals that can react with cellulose acetate, including, but not limited to, acids (e.g., sulfuric acid, nitric acid, acetic acid, hydrofluoric acid, hydrochloric acid, etc.), reducing agents (e.g., LiAlH4, NaBH4, H2 / Pt, etc.), Grignard reagents (e.g., CH3MgBr, etc.), transesterification agents, amines (e.g., R-NH3 such as CH3NH3), or any combination thereof. Exposure to plasma and / or ionized gas may react with the surface, create defects in the surface, or any combination thereof. The defects may increase the surface area of the fiber, which may result in higher loading and / or higher filtration efficacy in the final filter product.
[0045] Some embodiments of the present disclosure may involve applying a finish to the fibers. Suitable finishes may include, but are not limited to, at least one of: oil (e.g., mineral oil or a liquid petroleum derivative), water, an additive, or any combination thereof. Examples of suitable mineral oils may include, but are not limited to, colorless, transparent (i.e., clear) mineral oils having a viscosity of 80-95 SUS (Sabolt Universal Seconds) measured at 38° C. (100° F.). Examples of suitable emulsifiers may include, but are not limited to, sorbitan monolaurate, such as 20 (available from Croda, Wilmington, Del.), poly(ethylene oxide)sorbitan monolaurate, e.g. 20 (available from Croda Corporation, Wilmington, Delaware). The water may be demineralized water, deionized water, or other suitable filtered and treated water. The lubricant or finish may be applied by spraying or wiping. Generally, the lubricant or finish is added to the fibers before the fibers are formed into tow.
[0046] In some embodiments of the present disclosure, the finish may be applied as a neat finish or as a finish emulsion in water. As used herein, the term "neat finish" refers to a finish formulation without the addition of excess water. It should be noted that the finish formulation may include water. In some embodiments, the finish may be applied neat, followed by a separate application of water.
[0047] In some embodiments of the present disclosure, the finish emulsion may contain less than 98%, less than 95%, less than 92%, or less than 85% water. In some embodiments, it may be desirable to obtain fibers with a lower weight percentage of moisture (e.g., 5% to 25% w / w of the tow band) in subsequent steps where water is a contributor. The water content of the finish emulsion may be at least one parameter that can help achieve the stated weight percentage of moisture in the fiber. Thus, in some embodiments, the finish emulsion may contain less than 92% water, less than 85% water, or less than 75% water.
[0048] Tow
[0049] The present disclosure preferably includes forming a tow band from a plurality of fibers. In some embodiments, the tow band is from 10,000 to 100,000 total denier, for example, from 15,000 to 100,000, from 20,000 to 100,000, from 25,000 to 100,000, from 30,000 to 100,000, from 10,000 to 90,000, from 15,000 to 90,000, from 20,000 to 90,000, from 25,000 to 90,000, from 30,000 to 90,000, from 10,000 to 90,000, from 15,000 to 90,000, from 20,000 to 90,000, from 25,000 to 90,000, from 30 From 10,000 to 90,000, from 10,000 to 80,000, from 15,000 to 80,000, from 20,000 to 80,000, from 25,000 to 80,000, from 30,000 to 80,000, from 10,000 to 70,000, from 15,000 to 70,000, from 20,000 to 70,000, from 25,000 to 70,000, from 30,000 to 70,000, from 10,000 to 60,000, from 15,000 to 60,000, from 20,000 to 60,000, from 25,000 to 60,000, or from 30,000 to 60,000. As for the upper limit, the tow band can be less than 100,000 total denier, for example, less than 90,000, less than 80,000, less than 70,000, or less than 60,000. As for the lower limit, the tow band can be greater than 10,000 total denier, for example, greater than 15,000, greater than 20,000, greater than 25,000, or greater than 30,000.
[0050] In some embodiments, the tow may have a breaking strength between 3.5kg and 25kg, for example, from 3.5kg to 22.5kg, from 3.5kg to 20kg, from 3.5kg to 17.5kg, from 3.5kg to 15kg, from 4kg to 25kg, from 4kg to 22.5kg, from 4kg to 20kg, from 4kg to 17.5kg, from 4kg to 15kg, from 4.5kg to 25kg, from 4.5kg to 22.5kg, from 4.5kg to 20kg, from 4.5kg to 17.5kg, from 4.5kg to 15kg, from 5kg to 25kg, from 5kg to 22.5kg, from 5kg to 20kg, from 5kg to 17.5kg, or from 5kg to 15kg. In terms of upper limit, the tow can have a breaking strength of less than 25 kg, for example, less than 22.5 kg, less than 20 kg, less than 17.5 kg, or less than 15 kg. In terms of lower limit, the tow can have a breaking strength greater than 3.5 kg, for example, greater than 4 kg, greater than 4.5 kg, or greater than 5 kg.
[0051] In some embodiments of the present disclosure, the tow band may include more than one type of fiber. In some embodiments, the more than one type of fiber may vary based on dpf, cross-sectional shape, composition, treatment prior to forming the tow band, or any combination thereof. Examples of suitable additional fibers may include, but are not limited to, carbon fibers, activated carbon fibers, natural fibers, synthetic fibers, or any combination thereof.
[0052] Some embodiments of the present disclosure may include crimping the tow band to form a crimped tow band. The crimping of the tow band may involve using any suitable crimping technique known to those skilled in the art. These techniques may include various devices, including but not limited to stuffer boxes or gears. Non-limiting examples of crimping devices and their working mechanisms can be found in U.S. Patent Nos. 7,610,852 and 7,585,441, the entire contents and disclosures of which are incorporated herein by reference. Suitable stuffer box crimpers may have smooth crimper nip rollers, threaded or grooved crimper nip rollers, textured crimper nip rollers, upper platens, lower platens, or any combination thereof.
[0053] The configuration of the curl can play a role in the processability of the final package. Examples of curl configurations may include, but are not limited to, transverse, vertical, some degree between transverse and vertical, random, or any combination thereof. As used herein, the term "transverse" when describing the curl orientation refers to curls or fiber bends within the plane of the tow band. As used herein, the term "vertical" when describing the curl orientation refers to curls that protrude beyond the plane of the tow band and are perpendicular to the plane of the tow band. It should be noted that the terms transverse and vertical refer to the typical overall curl orientation and may have a deviation of + / - 30 degrees from the described configuration.
[0054] In some embodiments of the present disclosure, a crimped tow band may include fibers having a first crimped configuration and fibers having a second crimped configuration.
[0055] In some embodiments of the present disclosure, a curled tow band may include fibers having at least a vertical curl configuration near the edges and fibers having at least a transverse curl configuration near the center. In some embodiments, a curled tow band may include fibers having a vertical curl configuration near the edges and fibers having a transverse curl configuration near the center.
[0056] The crimped configuration can be important for the processability of the final package in subsequent processing steps, for example, a transverse crimped configuration can provide better fiber adhesion than a vertical crimped configuration unless additional steps are taken to improve adhesion. Methods for crimping a tow band having a substantially transverse crimped configuration are disclosed, for example, in U.S. Patent Nos. 2013 / 0115452 and 2015 / 0128964, each of which is incorporated herein in its entirety.
[0057] In some embodiments of the present disclosure, fibers can adhere to each other to provide better processability of final bag. Although adhesion additives can be used in combination with any curling structure, it may be advantageous to use adhesion additives together with vertical curling structure. In certain embodiments, adhesion may relate to adhesion additives on and / or in the fiber. Examples of such adhesion additives may include but are not limited to binders, adhesives, resins, tackifiers or any combination thereof. It should be noted that any additive described herein or other additives that can adhere two fibers together may be used, and these additives may include but are not limited to active particles, active compounds, ionic resins, zeolites, nanoparticles, ceramic particles, softeners, plasticizers, pigments, dyes, flavorings, aromatics, controlled release vesicles, surface modifiers, lubricants, emulsifiers, vitamins, peroxides, biocides, fungicides, antimicrobials, antistatic agents, flame retardants, defoamers, degradation agents, conductive modifiers, stabilizers or any combination thereof. Some embodiments of the present disclosure may involve adding a binder additive to fibers (in, on, or both) by incorporating the binder additive into a spinning solution, incorporating the binder additive into a finish, applying the binder additive to the fibers (before, after, and / or during formation of a tow band), applying the binder additive to a tow band (before, after, and / or during crimping), or any combination thereof.
[0058] Binder additives may be included in and / or on the fibers in a concentration sufficient to adhere the fibers together at multiple contact points to provide better processability of the final package. The concentration of the binder additive to be used may depend on the type of binder additive and the adhesion strength provided by the binder additive. In some embodiments, the concentration of the binder additive may range from a lower limit of 0.01%, 0.05%, 0.1%, or 0.25% to an upper limit of 5%, 2.5%, 1%, or 0.5% (by weight of the tow band in the final package). It should be noted that for additives used for more than just adhesion, the concentration in the tow band in the final package may be higher, such as 25% or less.
[0059] In addition, some embodiments of the present disclosure may involve heating the fibers before, after, and / or during crimping. While the heating may be used in conjunction with any crimping configuration, it may be advantageous to use the heating with a vertical crimping configuration. The heating may involve exposing the fibers of the tow band to steam, an atomized compound (e.g., a plasticizer), a liquid, a heating fluid, a direct heat source, an indirect heat source, a radiation source that generates heat for additives (e.g., nanoparticles) in the fibers, or any combination thereof.
[0060] Some embodiments of the present disclosure may include conditioning the curled tow band. Conditioning may be used to achieve a curled tow band having a residual acetone content of 0.5% or less w / w of the curled tow band. Conditioning may be used to achieve a curled tow band having a residual water content of 8% or less w / w of the curled tow band. Conditioning may involve exposing the fibers of the curled tow band to steam, an atomized compound (e.g., a plasticizer), a liquid, a heated fluid, a direct heat source, an indirect heat source, a radiation source that generates heat to an additive (e.g., nanoparticles) in the fibers, or any combination thereof.
[0061] UCE is the amount of work required to uncrimp the fiber. As reported below, UCE was sampled prior to baling (i.e., after drying and before baling). As used herein, UCE is measured as follows: Using a preheated (20 minutes prior to routine calibration) Instron tensile tester (Model 1130, crosshead gear - gear numbers R1940-1 and R940-2, Instron Series IX - Version 6 data acquisition and analysis software, Instron 50 kg maximum capacity load cell, Instron top roller assembly, 1" x 4" x 1 / 8" thick high grade Buna-N 70 Shore A Durometer rubber grip face), a preconditioned tow sample of approximately 76 cm in length (preconditioned for 24 hours at 22°C ± 2°C and 60% ± 2% relative humidity) is looped and evenly distributed around the center of the top roller, pre-stretched by gently pulling to 100 g ± 2 g (according to the readout display), and each end of the sample is clamped in the lower grip (at the highest available pressure, but not exceeding the manufacturer's recommendation) to achieve a 50 cm gauge length (the gauge length is measured from the top of the rubber grip), and then tested at a crosshead speed of 30 cm / min until fracture. Repeat this test until three acceptable tests are obtained, and report the average of the three data points for these tests. Energy (E) limit is 0. 220kg and 10.0kg. Displacement (D) has a preset point of 10.0kg. UCE is calculated by the following formula: UCE (gcm / cm) = (E*1000) / ((D*2) + 500). Breaking strength can be calculated using the same test and the following equation BS = L (where L is the load at maximum load (kg)). In certain embodiments of the present disclosure, the UCE value (in gcm / cm) can range from 190 to 400, such as 200 to 300, such as 290. In certain embodiments of the present disclosure, the breaking strength can range from 3.5kg to 25kg, such as 4kg to 20kg, 4.5kg to 15kg, or 5kg to 12kg.
[0062] Tow Package
[0063] Some embodiments of the present disclosure may include packing a curled tow band to produce a bag. In some embodiments, packing may involve placing the curled tow band in a certain pattern in a tank, for example, laying, depositing or arranging. It should be noted that tanks are generally used to refer to containers that can be of any shape (preferably square or rectangular) and of any material. As used herein, the term "pattern" refers to any design that may or may not change during placement. In some embodiments of the present disclosure, the pattern may be roughly zigzag, with a periodicity of 0.5 cycles / feet to 6 cycles / feet. In some embodiments, placement may involve puddling the curled tow band with a puddling index of 10m / m to 40m / m. As used herein, the term "puddling" refers to laying the tow band at least partially on itself so as to place a tow band of an actual length greater than the linear distance of the tow band. As used herein, the term "puddling index" refers to the length of the tow band on each linear distance of the tow band.
[0064] In some embodiments of the present disclosure, packaging may involve compressing a curled filament bundle that has been placed in a suitable container. In some embodiments, packaging may involve packaging the compressed curled filament bundle. In some embodiments, the package may include at least one component, such as a packaging material, a vacuum port (for releasing vacuum and / or evacuating), a fixing element, or any combination thereof. Suitable packaging materials may include, but are not limited to, breathable materials, airtight materials, films (e.g., polymer films, polyethylene films, plastic wrap films), heat-shrinkable films, cardboard, wood, woven materials (i.e., fabrics composed of two sets of yarns, which are interwoven with each other to form a fabric), non-woven materials (i.e., textile fiber components held together by mechanical or chemical means in the form of random webs or mats, such as fused thermoplastic fibers), foil materials (e.g., metal materials), etc., or any combination thereof. Suitable fixing elements may include, but are not limited to Pins, hooks, straps (e.g., woven, nonwoven, fabric, and / or metal), adhesives, tapes, melt bonding, etc., or any combination thereof. In some embodiments, at least a portion of the package (including any component thereof) may be reusable.
[0065] In some embodiments of the present disclosure, the fiber may include an additive. Some embodiments of the present disclosure may involve application during any of the steps outlined above or between any of the steps outlined above. Examples of suitable locations for incorporating additives may include, but are not limited to, in the spinning solution, in the finish, in the conditioning, or any combination thereof. In addition, the additive may be applied to the fiber at any point before forming the tow band, applied to the fiber during and / or after forming the tow band, applied to the fiber during and / or after crimping the tow band, applied to the fiber during and / or after conditioning, or any combination thereof.
[0066] Suitable additives may include, but are not limited to, active particles, active compounds, ion exchange resins, zeolites, nanoparticles, ceramic particles, softeners, plasticizers, pigments, dyes, flavoring agents, fragrances, controlled release vesicles, binders, adhesives, tackifiers, surface modifiers, lubricants, emulsifiers, vitamins, peroxides, biocides, fungicides, antimicrobial agents, antistatic agents, flame retardants, defoamers, degraders, conductivity modifiers, stabilizers, or any combination thereof. In some embodiments, fibers containing additives can be achieved by including the additives in the spinning solution; by applying the additives to the fibers before, after, and / or during the formation of the tow band; by applying the additives to the fibers before, after, and / or during the curling of the tow band; by applying the additives to the fibers before, after, and / or during the conditioning of the curled tow band; and any combination thereof. It should be noted that application includes, but is not limited to, dipping, impregnating, immersing, soaking, rinsing, washing, smearing, coating, rinsing, sprinkling, spraying, placing, dusting, spraying, pasting, and any combination thereof. Furthermore, it should be noted that the applications include, but are not limited to, surface treatments, infusion treatments where the additive is at least partially incorporated into the fiber, and any combination thereof.
[0067] Those skilled in the art who have the benefit of this disclosure will appreciate that the concentration of the additive will depend at least on the composition of the additive, the size of the additive, the purpose of the additive, the point in the process at which the additive is included, and the size of the fiber. As a non-limiting example, the additive may be present in the spinning solution in an amount ranging from 0.01% to 10% by weight of the polymer. As another non-limiting example, an additive comprising microparticles may be included such that the fiber comprises 0.01% to 10% by volume of the fiber.
[0068] Suitable active particles may include, but are not limited to, nanoscale carbon particles, carbon nanotubes having at least one wall, carbon nanohorns, bamboo-like carbon nanostructures, fullerenes, fullerene aggregates, graphene, several layers of graphene, graphene oxide, iron oxide nanoparticles, nanoparticles, metal nanoparticles, gold nanoparticles, silver nanoparticles, metal oxide nanoparticles, aluminum oxide nanoparticles, magnetic nanoparticles, paramagnetic nanoparticles, superparamagnetic nanoparticles, gadolinium oxide nanoparticles, hematite nanoparticles, magnetite nanoparticles, gadolinium nanotubes, endohedral fullerenes, Gd@C60, core-shell nanoparticles, onion-shaped nanoparticles, nanoshells, onion-shaped iron oxide nanoparticles, activated carbon, ion exchange resins, desiccant, silicate, molecular sieve, silica gel, activated alumina, zeolite, perlite, sepiolite, fuller's earth, magnesium silicate, metal oxides, iron oxide, activated carbon, and any combination thereof.
[0069] Suitable active particles can have at least one dimension less than one nanometer, such as graphene, as large as particles with a diameter of 5000 microns. The lower limit range of the size of active particles in at least one dimension can be: 0.1 nanometer, 0.5 nanometer, 1 nanometer, 10 nanometers, 100 nanometers, 500 nanometers, 1 micron, 5 microns, 10 microns, 50 microns, 100 microns, 150 microns, 200 microns and 250 microns. The upper limit range of the size of active particles in at least one dimension can be: 5000 microns, 2000 microns, 1000 microns, 900 microns, 700 microns, 500 microns, 400 microns, 300 microns, 250 microns, 200 microns, 150 microns, 100 microns, 50 microns, 10 microns and 500 nanometers. Any combination of the above lower limit and upper limit can be suitable for use in the present disclosure, wherein the selected maximum size is greater than the selected minimum size. In certain embodiments, active particles can be a mixture of particle sizes ranging from the above lower limit and upper limit. In some embodiments, the size of the active particles can be multimodal.
[0070] Suitable active compounds may include, but are not limited to, malic acid, potassium carbonate, citric acid, tartaric acid, lactic acid, ascorbic acid, polyethyleneimine, cyclodextrin, sodium hydroxide, sulfamic acid, sodium sulfamate, polyvinyl acetate, carboxylated acrylates, and any combination thereof.
[0071] Suitable ion exchange resins may include, but are not limited to, polymers having backbones such as styrene-divinylbenzene (DVB) copolymers, acrylates, methacrylates, phenol formaldehyde condensates, and epichlorohydrinamine condensates; multiple charged functional groups attached to the polymer backbone; and any combination thereof.
[0072] Zeolites may include crystalline aluminosilicates having uniform, molecular-sized pores (e.g., channels or chambers). Zeolites may include natural and synthetic materials. Suitable zeolites may include, but are not limited to, zeolite BETA (Na7(A17Si57O128) tetragonal), zeolite ZSM-5 (Nan(AlnSi96-nO192)16 H2O, wherein n<27), zeolite A, zeolite X, zeolite Y, zeolite KG, zeolite ZK-5, zeolite ZK-4, mesoporous silicates, SBA-15, MCM-41, MCM48 modified by 3-aminopropylsilyl, aluminophosphates, mesoporous aluminosilicates, other related porous materials (e.g., such as mixed oxide gels), or any combination thereof.
[0073] Suitable nanoparticles may include, but are not limited to, nanoscale carbon particles such as carbon nanotubes with any number of walls, carbon nanohorns, bamboo-like carbon nanostructures, fullerenes and fullerene aggregates, and graphene (including several layers of graphene and graphene oxide); metal nanoparticles such as gold and silver; metal oxide nanoparticles such as aluminum oxide and silicon dioxide; magnetic, paramagnetic and superparamagnetic nanoparticles such as gadolinium oxide, iron oxides of various crystal structures such as hematite and magnetite, 12nm Fe3O4, gadolinium nanotubes, and embedded fullerenes such as Gd@C60; and core-shell and onion-shaped nanoparticles such as gold and silver nanoshells, onion-shaped iron oxide, and other nanoparticles or microparticles having an outer shell of any of the materials described; or any combination of the above (including activated carbon). It should be noted that nanoparticles may include nanorods, nanospheres, nanometers, nanowires, nanostars (such as nanotripods and nanotetrapods), hollow nanostructures, hybrid nanostructures formed by connecting two or more nanoparticles, and non-nanoparticles with nanocoatings or nanothick walls. It should be further noted that nanoparticles may include functionalized derivatives of nanoparticles, including but not limited to nanoparticles that have been functionalized covalently and / or non-covalently (e.g., π-stacking, physical adsorption, ionic association, van der Waals association, etc.). Suitable functional groups may include but are not limited to moieties comprising amines (1°, 2°, or 3°), amides, carboxylic acids, aldehydes, ketones, ethers, esters, peroxides, silyl groups, organosilanes, hydrocarbons, aromatic hydrocarbons, and any combination thereof; polymers; chelating agents such as ethylenediaminetetraacetic acid, diethylenetriaminepentaacetic acid, nitrilotriacetic acid, and structures comprising pyrrole rings; and any combination thereof. The functional groups may enhance the removal of smoke components and / or enhance the incorporation of nanoparticles into the porous material.
[0074] Suitable softeners and / or plasticizers may include, but are not limited to, water, triacetin, triethyl citrate, dimethoxy-ethyl phthalate, dimethyl phthalate, diethyl phthalate, glycolic acid methylphthalyl ethyl ester, o-phenylphenyl-(bis)phenyl phosphate, 1,4-butanediol diacetate, diacetate, dipropionate of triethylene glycol, dibutyrate of triethylene glycol, dimethoxyethyl phthalate, triethyl citrate, triacetyl glycerol, and the like, any derivatives thereof, and any combination thereof. Those skilled in the art who have the benefit of this disclosure should understand the concentration of plasticizers used as fiber additives. As a non-limiting example, a plasticizer may be added to the spinning solution in an amount sufficient to prevent the fiber surface from rupturing or bursting when the adsorbed solvent is suddenly discharged thermally.
[0075] As used herein, dye refers to compounds and / or particles that impart color and provide a surface treatment to fibers. Suitable dyes may include, but are not limited to, liquid and / or granular forms. Dyes (cationic dyes, available from Clariant Services) (e.g., Bright yellow K-6G liquid, Yellow K-4GL liquid, Yellow K-GL liquid, Orange K-3GL liquid, Scarlet K-2GL liquid, Red K-3BN liquid, Blue K-5R liquid, Blue K-RL liquid, Blue-green K-RL liquid / granules, Brown K-BL liquid), Dyes (auxochromes, available from BASF) (eg, Yellow 3GL, Fastusol C Blue 74L).
[0076] Suitable flavoring agent can be any flavoring agent suitable for smoking device filter, including those flavoring agents that give smoke flow taste and / or fragrance. Suitable flavoring agent can include but is not limited to organic material (or natural flavor particles), carrier of natural flavor, carrier of artificial flavor and any combination thereof. Organic material (or natural flavor particles) include but are not limited to tobacco, cloves (for example, clove powder and cloves), cocoa etc. Natural and artificial flavors can include but are not limited to menthol, cloves, cherry, chocolate, orange, mint, mango, vanilla, cinnamon, tobacco etc. Such fragrance can be provided by menthol, anethole (licorice), anisole, limonene (citrus), eugenol (cloves) etc. or any combination thereof. In certain embodiments, more than one flavoring agent can be used, including any combination of flavoring agents provided herein. These flavoring agents can be placed in tobacco column or in filter segment. In addition, in certain embodiments, the porous material of the present disclosure can include flavoring agent. The amount included will depend on the desired fragrance level in the smoke of all filter segments, the length of smoking device, the type of smoking device, the diameter of smoking device and other factors known to those skilled in the art.
[0077] Suitable fragrances may include, but are not limited to, methyl formate, methyl acetate, methyl butyrate, ethyl acetate, ethyl butyrate, isoamyl acetate, amyl butyrate, amyl valerate, octyl acetate, myrcene, geraniol, nerol, citral, citronellal, citronellol, linalool, nerolidol, limonene, camphor, terpineol, α-ionone, thujone, benzaldehyde, eugenol, cinnamaldehyde, ethyl maltol, vanilla, anisole, anethole, estragole, thymol, furanone, methanol, or any combination thereof.
[0078] Suitable adhesives may include, but are not limited to, polyolefins, polyesters, polyamides (or nylons), polyacrylates, polystyrenes, polyethylene compounds, polytetrafluoroethylene (PTFE), polyetheretherketone (PEEK), any copolymers thereof, any derivatives thereof, and any combinations thereof. Non-fibrous plasticized cellulose derivatives may also be suitable for use as binder particles in the present disclosure. Examples of suitable polyolefins may include, but are not limited to, polyethylene, polypropylene, polybutene, polymethylpentene, etc., any copolymers thereof, any derivatives thereof, and any combinations thereof. Examples of suitable polyethylene may include, but are not limited to, ultra-high molecular weight polyethylene, extremely high molecular weight polyethylene, high molecular weight polyethylene, low density polyethylene, linear low density polyethylene, high density polyethylene, etc., any copolymers thereof, any derivatives thereof, and any combinations thereof. Examples of suitable polyesters may include, but are not limited to, polyethylene terephthalate, polybutylene terephthalate, polycyclohexylene dimethylene terephthalate, polytrimethylene terephthalate, etc., any copolymers thereof, any derivatives thereof, and any combinations thereof. The example of suitable polyacrylate may include but is not limited to polymethyl methacrylate, etc., any copolymer thereof, any derivative thereof, and any combination thereof. The example of suitable polystyrene may include but is not limited to polystyrene, acrylonitrile-butadiene-styrene, styrene-acrylonitrile, styrene-butadiene, styrene-maleic anhydride, etc., any copolymer thereof, any derivative thereof, and any combination thereof. The example of suitable polyethylene compound may include but is not limited to ethylene vinyl acetate, ethylene vinyl alcohol, polyvinyl chloride, etc., any copolymer thereof, any derivative thereof, and any combination thereof. The example of suitable cellulosic plastic may include but is not limited to cellulose acetate, cellulose acetate butyrate, plasticized cellulose, cellulose propionate, ethyl cellulose, etc., any copolymer thereof, any derivative thereof, and any combination thereof. In some embodiments, the binder particles may include any copolymer, any derivative, or any combination of the binders listed above. In addition, the binder particles may be impregnated with and / or coated with any combination of additives disclosed herein.
[0079] Suitable viscosity increasing agents may include, but are not limited to, methylcellulose, ethylcellulose, hydroxyethylcellulose, carboxymethylcellulose, carboxyethylcellulose, water-soluble cellulose acetate, amides, diamines, polyesters, polycarbonates, silyl-modified polyamide compounds, polyurethanes, polyurethanes, natural resins, shellac, acrylic acid polymers, 2-ethylhexyl acrylate, acrylate polymers, acrylic acid derivative polymers, acrylic acid homopolymers, acrylate homopolymers, poly(methyl acrylate), poly(butyl acrylate), poly(2-ethylhexyl acrylate), acrylate copolymers, methacrylic acid derivative polymers, methacrylic acid homopolymers, methacrylate homopolymers, poly(methacrylic acid) acrylate), poly(methyl methacrylate), poly(butyl methacrylate), poly(2-ethylhexyl methacrylate), acrylamido-methyl-propane sulfonate polymer, acrylamido-methyl-propane sulfonate derivative polymer, acrylamido-methyl-propane sulfonate copolymer, acrylic acid / acrylamido-methyl-propane sulfonate copolymer, benzyl coconut oil di-(hydroxyethyl) quaternary amine, p-tert-amylphenol condensed with formaldehyde, dialkylaminoalkyl (meth)acrylate, acrylic acid amide, N-(dialkylaminoalkyl)acrylamide, methacrylamide, hydroxyalkyl (meth)acrylate, methacrylic acid, acrylic acid, hydroxyethyl acrylate, etc., any derivatives thereof, or any combination thereof.
[0080] Suitable lubricants may include, but are not limited to, ethoxylated fatty acids (e.g., the reaction product of ethylene oxide and nonanoic acid to form poly(ethylene glycol) ("PEG") monononanoate; the reaction product of ethylene oxide and coconut fatty acid to form PEG monolaurate), etc., or any combination thereof. Lubricants may also be selected from non-water-soluble materials such as synthetic hydrocarbon oils, alkyl esters (e.g., tridecyl stearate, which is the reaction product of tridecanol and stearic acid), polyol esters (e.g., trimethylolpropane trinonanoate and pentaerythritol tetranonanoate), etc., or any combination thereof.
[0081] Suitable emulsifiers may include, but are not limited to, sorbitan monolaurate, e.g. 20 (available from Croda Corporation, Wilmington, Delaware), poly(ethylene oxide) sorbitan monolaurate, e.g. 20 (available from Croda Corporation, Wilmington, Delaware).
[0082] Suitable vitamins may include, but are not limited to, vitamin A, vitamin B1, vitamin B2, vitamin C, vitamin D, vitamin E, or any combination thereof.
[0083] Suitable antimicrobial agents may include, but are not limited to, antimicrobial metal ions, chlorhexidine, chlorhexidine salts, triclosan, polymyxins, tetracyclines, aminoglycosides (e.g., gentamicin), rifampicin, bacitracin, erythromycin, neomycin, chloramphenicol, miconazole, quinolones, penicillins, nonoxynol 9, fusidic acid, cephalosporins, mupirocin, metronidazole a secropin, antimicrobial peptides, bacteriocins, defensins, nitrofuracil, mafenide, acyclovir, vancomycin, clindamycin, lincomycin, sulfonamides, norfloxacin, pefloxacin, nalidizic acid, acid), oxalic acid, enoxacin acid, ciprofloxacin, polyhexamethylene biguanide (PHMB), PHMB derivatives (e.g., biodegradable biguanides such as polyethylene hexamethylene biguanide (PEHMB)), chlorhexidine gluconate, chlorhexidine hydrochloride, ethylenediaminetetraacetic acid (EDTA), EDTA derivatives (e.g., disodium EDTA or tetrasodium EDTA), etc., and any combination thereof.
[0084] Antistatic agents may include any suitable anionic, cationic, amphoteric or nonionic antistatic agents. Anionic antistatic agents may generally include, but are not limited to, alkali sulfates, alkali phosphates, phosphate esters of alcohols, phosphate esters of ethoxylated alcohols, or any combination thereof. Examples may include, but are not limited to, alkali-neutralized phosphate esters (e.g., 5559 or 5576, available from Henkel Corporation, Mauldin, SC). Cationic antistatic agents generally can include, but are not limited to, quaternary ammonium salts and imidazolines having a positive charge. Examples of nonionics include poly(oxyalkylene) derivatives, for example, ethoxylated fatty acids such as 2650 (ethoxylated fatty acids, available from Henkel Corp., Mauldin, SC), ethoxylated fatty alcohols such as 5964 (ethoxylated lauryl alcohol, available from Henkel Corporation, Mauldin, South Carolina), ethoxylated fatty amines such as 6606 (ethoxylated tallow amine, available from Henkel Corp., Mauldin, SC), alkanolamides such as 6545 (diethanolamine oleate, available from Henkel Corporation, Mauldin, South Carolina), or any combination thereof. Anionic and cationic materials tend to be more effective antistatic agents.
[0085] As used herein, pigment refers to compounds and / or particles that impart color and are incorporated throughout the fiber. Suitable pigments may include, but are not limited to, silica, tartrazine, E102, phthalocyanine blue, phthalocyanine green, quinacridone, floretate diimide, dioxazine, peronone disazo pigments, anthraquinone pigments, carbon black, metal powders, iron oxide, ultramarine, calcium carbonate, kaolin, aluminum hydroxide, barium sulfate, zinc oxide, aluminum oxide, or any combination thereof.
[0086] Titanium dioxide is a commonly used pigment in conventional cellulose acetate tow bands. Conventional cellulose acetate tow bands may contain titanium dioxide in an amount greater than 0.1 wt.%, for example, greater than 0.3 wt.%, greater than 0.5 wt.%, greater than 1 wt.%, or greater than 2 wt.%, or as described above, however, the use of titanium dioxide may cause negative side effects, including manufacturing and commercial problems. Therefore, the cellulose acetate tow band according to the present disclosure preferably does not contain titanium dioxide as an additive. In some embodiments, the tow band contains less than 0.1 wt.% (1000 ppm) of titanium dioxide, for example, less than 0.01 wt.% (100 ppm), less than 90 ppm, less than 50 ppm, or less than 25 ppm. In terms of the lower limit, the tow band may contain greater than 0 ppm of titanium dioxide, for example, greater than 1 ppm, greater than 5 ppm, greater than 10 ppm, or greater than 15 ppm. In terms of ranges, the tow band may contain from 0 ppm to 0.1 wt. % titanium dioxide, e.g., from 0 ppm to 100 ppm, from 0 ppm to 90 ppm, from 0 ppm to 50 ppm, from 0 ppm to 25 ppm, from 1 ppm to 0.1 wt. %, from 1 ppm to 100 ppm, from 1 ppm to 90 ppm, from 1 ppm to 50 ppm, from 1 ppm to 25 ppm, from 5 ppm to 0.1 wt. %, from 5 ppm to 100 ppm, From 5ppm to 90ppm, from 5ppm to 50ppm, from 5ppm to 25ppm, from 10ppm to 0.1wt.%, from 10ppm to 100ppm, from 10ppm to 90ppm, from 10ppm to 50ppm, from 10ppm to 25ppm, from 15ppm to 0.1wt.%, from 15ppm to 100ppm, from 15ppm to 90ppm, from 15ppm to 50ppm, or from 15ppm to 25ppm. In some preferred embodiments, the filamentary band is substantially free of titanium dioxide. In some aspects, titanium dioxide is not intentionally added to the filamentary band. Any amount of titanium dioxide detected by the methods disclosed herein is accidental, meaning that they are impurities in other components of the filamentary band.
[0087] Conventional methods of measuring titanium dioxide concentration in cellulose acetate tow bands are unable to accurately and / or precisely measure such low concentrations of titanium dioxide. However, the present inventors have developed a method for determining the titanium dioxide content in cellulose tow bands, even when titanium dioxide is present in an amount less than 0.1 wt.%.
[0088] One method of determining titanium dioxide content is by ashing a sample of cellulose acetate tow. The present inventors have discovered that the cellulose acetate tow disclosed herein has a significantly low ash weight. In some embodiments, the cellulose acetate tow has an ash weight of less than 0.1% of the tow, e.g., less than 0.09%, less than 0.08%, less than 0.07%, less than 0.06%, or less than 0.05%.
[0089] In addition, the inventors of the present invention have found that the cellulose acetate tow disclosed herein has a significantly low ash weight relative to the ash weight of conventional cellulose acetate tow tapes containing conventional amounts of titanium dioxide (e.g., cellulose acetate tow tapes containing greater than 0.1 wt.%, greater than 1 wt.%, greater than 2 wt.%, greater than 3 wt.%, greater than 4 wt.%, or greater than 5 wt.% titanium dioxide). Conventional cellulose acetate may have an ash weight of greater than 0.1% of the tow, for example, greater than 0.2%, greater than 0.3%, or greater than 0.4%. In some embodiments, the cellulose acetate tow tapes disclosed herein have an ash weight that is less than 25% of the ash weight of conventional cellulose acetate fibers, for example, less than 20%, less than 15%, or less than 10%. This difference in ash weight provides a qualitative indicator for determining the titanium dioxide content in the cellulose acetate tow tape.
[0090] The inventors of the present invention have also developed another method for quantitatively determining the titanium dioxide concentration in a tow band by ashing. An example of this method is described in further detail below.
[0091] Another method of determining titanium dioxide content is by observing the titanium particle count density via, for example, cross-sectional image analysis. Because individual titanium dioxide particles can be seen within each fiber of the cellulose acetate tow, the average number of titanium particles per single fiber denier can be determined. Conventional acetate tow bands typically have from 15 to 50 titanium dioxide particles per fiber denier. In some embodiments, the cellulose acetate tow bands disclosed herein have less than 10.0 titanium dioxide particles per fiber denier, e.g., less than 8.0, less than 5.0, less than 2.0, or less than 1.0.
[0092] Cross-sectional image analysis of conventional cellulose acetate fibers and cellulose acetate fibers according to the present disclosure are shown in FIGS. 1A and 1B , respectively.
[0093] Measuring the Titanium Dioxide Content of Cellulose Acetate
[0094] As described above, previous efforts to produce cellulose acetate tow having a reduced titanium dioxide content (e.g., cellulose acetate tow that is substantially free of titanium dioxide) have been limited due to inadequacies of conventional methods for analytical measurement and / or quality control. In particular, the present inventors have discovered that it is difficult to produce cellulose acetate tow having a low titanium dioxide content of satisfactory quality because certain conventional analytical methods cannot be used for such tow. One example of an analytical method that has limited the development of the cellulose acetate tow described herein is a method for measuring the titanium dioxide content of the cellulose acetate tow.
[0095] The inventors of the present invention have discovered that conventional methods of measuring the titanium dioxide content of cellulose acetate tow (e.g., by X-ray diffraction techniques) are only effective for measuring relatively high concentrations of titanium dioxide in the tow, e.g., greater than 0.1 wt.%, greater than 1 wt.%, greater than 2 wt.%, greater than 3 wt.%, greater than 4 wt.%, or greater than 5 wt.% titanium dioxide. However, conventional methods are unable to adequately measure low concentrations of titanium dioxide. Accurate measurement of titanium dioxide content is necessary, for example, for quality control purposes. Accurate measurement of titanium dioxide content may also be necessary to comply with product additive requirements and potential regulations. These requirements may dictate a maximum titanium dioxide content in cellulose acetate tow, and therefore, it is necessary to accurately and precisely determine the content of titanium dioxide, particularly at low concentrations of titanium dioxide.
[0096] As described above, the present disclosure relates to a novel method for measuring the titanium dioxide content of cellulose acetate, which is suitable for measuring low concentrations of titanium dioxide. This novel method includes preparing a sample of cellulose acetate for measurement; ashing the sample to form an ashed sample; dissolving the ashed sample to form a sample solution; titrating a blank solution with a titanium standard; and comparing the titrated blank solution with the sample solution.
[0097] The method for measuring the titanium dioxide content of cellulose acetate disclosed herein is applicable to cellulose acetate samples having relatively low titanium dioxide contents. In some embodiments, the method is applicable to cellulose acetate samples having less than 0.1 wt.% (1000 ppm) of titanium dioxide, e.g., less than 900 ppm, less than 750 ppm, less than 500 ppm, less than 250 ppm, or less than 100 ppm. In terms of lower limits, the method may be applicable to cellulose acetate samples having a titanium dioxide content of 15 ppm or greater, e.g., greater than 20 ppm, greater than 25 ppm, or greater than 30 ppm. In terms of ranges, the method is applicable to cellulose acetate samples having a titanium dioxide content of from 15 ppm to 1000 ppm, e.g., from 15 ppm to 900 ppm, from 15 ppm to 750 ppm, from 15 ppm to 500 ppm, from 15 ppm to 250 ppm, from 15 ppm to 100 ppm, from 20 ppm to 1000 ppm, from 20 ppm to 900 ppm, from 20 ppm to 750 ppm, from 20 ppm to 500 ppm, from 20 ppm to 250 ppm, From 20 ppm to 100 ppm, from 25 ppm to 1000 ppm, for example from 25 ppm to 900 ppm, from 25 ppm to 750 ppm, from 25 ppm to 500 ppm, from 25 ppm to 250 ppm, from 25 ppm to 100 ppm, from 30 ppm to 1000 ppm, for example from 30 ppm to 900 ppm, from 30 ppm to 750 ppm, from 30 ppm to 500 ppm, from 30 ppm to 250 ppm, or from 30 ppm to 100 ppm.
[0098] In some embodiments of the method, the cellulose acetate sample analyzed by the disclosed method is in the form of cellulose acetate tow. The cellulose acetate tow analyzed by the disclosed method may include cellulose acetate fibers having a denier per filament of less than 12.5. The cellulose acetate tow analyzed by the disclosed method may include cellulose acetate fibers having a denier per filament of greater than 12.5.
[0099] In some embodiments, the cellulose acetate sample analyzed by the disclosed methods is a dope solution of cellulose acetate. In some embodiments, cellulose acetate is analyzed both as a dope solution and as cellulose acetate tow.
[0100] The method of measuring the titanium dioxide content of cellulose acetate includes preparing a sample of cellulose acetate for measurement. Preparing the sample as disclosed herein can ensure the precision and accuracy of determining the titanium dioxide content. Importantly, in embodiments in which the disclosed method is used to measure the titanium dioxide of a cellulose acetate tow sample, the sample is prepared as disclosed herein to remove external finishes and / or any impurities that may affect the measurement. In some embodiments, the sample is prepared according to the standard test method for fiber extraction defined in ASTM D2257-98 (2012), which is incorporated herein in its entirety.
[0101] In some embodiments, preparing a sample of cellulose acetate for measurement includes treating cellulose acetate with an organic non-solvent. The organic non-solvent used to treat the sample is not particularly limited and may include, for example, alcohols, ethers, ketones, esters, and combinations thereof. The organic non-solvent may be any organic non-solvent suitable for removing external finishing agents and / or other impurities from cellulose acetate. In some embodiments, the organic non-solvent may be an alcohol, such as ethanol, n-propanol, isopropanol, n-butanol, 2-butanol, isobutanol, tert-butanol, or a combination thereof. In some embodiments, the organic non-solvent may be an ether, such as diethyl ether, methyl tert-butyl ether, isopropyl ether, or ethylene glycol methyl ether. In some embodiments, the organic non-solvent may be a ketone, such as 2-pentanone. In some embodiments, the organic non-solvent may be an ester, such as isopropyl acetate or isobutyl acetate. In some embodiments, the organic non-solvent is a combination of any of these solvents.
[0102] The act of treating the cellulose acetate sample with an organic non-solvent is not particularly limited and generally includes subjecting the sample to an organic non-solvent and then drying the sample. Many methods of treating samples with non-solvents are known in the art and can be used here to treat cellulose acetate samples with organic non-solvents. In some embodiments, the cellulose acetate sample can be simply washed with an organic non-solvent. In other embodiments, the sample can be immersed in an organic non-solvent with or without stirring. The stirring can be manual, such as stirring by hand, or mechanical, such as in a mechanical oscillator. In some embodiments, the treatment of the cellulose acetate sample can include any combination of these and / or other known methods of treating samples with non-solvents. Similarly, many methods of drying samples that have been treated with organic non-solvents are known in the art and can be used here. For example, the treated sample can be squeezed, filtered and / or drained to remove excess non-solvent and / or air dried, dried in a vacuum, dried in a desiccator, and / or dried in an oven.
[0103] In embodiments where the presently disclosed method is used to measure titanium dioxide in a cellulose acetate dope solution, removal of the external finish is generally not required. In these embodiments, preparing the sample generally involves only collecting a sample of cellulose acetate, e.g., in a test tube. Preferably, preparing the cellulose acetate dope solution removes excess solvent, thereby improving ashing of the sample.
[0104] The method of measuring the titanium dioxide content of cellulose acetate includes ashing a sample of cellulose acetate to form an ashed sample. As described above, the sample of cellulose acetate as described herein and to which the methods disclosed herein are applicable has an ash weight that is less than the ash weight of conventional cellulose acetate (e.g., cellulose acetate containing a higher content of titanium dioxide). The present inventors have developed the methods disclosed herein to measure the titanium dioxide content after discovering that the titanium dioxide content affects the accuracy of the ash content of cellulose acetate.
[0105] In general, a sample of cellulose acetate prepared by ashing according to the methods disclosed herein includes burning the sample. Many methods of burning cellulose acetate are known in the art and can be used herein. In some embodiments, for example, a sample prepared by ashing includes igniting the sample, for example, by burning with a Bunsen burner. In another embodiment, a sample prepared by ashing includes burning the sample in a furnace (e.g., a muffle furnace) or an oven. In some embodiments, a sample prepared by ashing includes a variety of combustion methods, for example, both igniting the prepared sample and burning the prepared sample in a furnace. The amount of time for burning the prepared sample is not particularly limited. In some embodiments, the sample can be burned for greater than 20 minutes, for example, greater than 30 minutes, greater than 40 minutes, or greater than 60 minutes. Preferably, the prepared sample burns the time required to completely ash the sample.
[0106] Other methods of quantifying samples of ashed cellulose acetate are known to those skilled in the art and may also be used herein.
[0107] In some embodiments, the cellulose acetate sample is further processed after combustion. This may include treating the burned sample with a salt. The burned sample is solid, and treating the sample with a salt as described herein can improve and / or ensure complete dissolution prior to subsequent quantitative analysis. Such methods for improving the solubility of solid samples are known in the art, and any known salt can be used. In some embodiments, the salt is an acid salt of an alkali metal, preferably a salt of an inorganic acid. Examples of suitable acid salts include sodium pyrosulfate, sodium sulfate, sodium bisulfate, potassium pyrosulfate, potassium bisulfate, potassium sulfate and potassium bisulfate, and combinations thereof.
[0108] In some embodiments, the cellulose acetate sample is combusted after treatment. Any combustion method known in the art, including those discussed above, can be used to combust the cellulose acetate after treatment. In preferred embodiments, combustion liquefies the solid sample after treatment.
[0109] The method for measuring the titanium dioxide content of cellulose acetate includes dissolving the ashed sample to form a sample solution. The solvent for dissolving the ashed sample is not particularly limited, and any solvent suitable for the analysis and uses described herein can be used. In some embodiments, the ashed sample is dissolved in water, preferably distilled water. In some embodiments, the ashed sample is dissolved in an acid, preferably an inorganic acid. Examples of suitable inorganic acids include hydrochloric acid, nitric acid, phosphoric acid, sulfuric acid, boric acid, and combinations thereof. In some embodiments, the ashed sample is dissolved in both water and acid, for example, dissolved in water and then diluted in acid, or dissolved in acid and then diluted in water. In some embodiments, the dissolution of the ashed sample can be used to effectively transfer the ashed sample to another container.
[0110] In some embodiments, the sample solution is further processed. In some embodiments, hydrogen peroxide is added to the sample solution. The inventors of the present invention have discovered that hydrogen peroxide is a chromogenic reagent that reacts with the sample solution to produce a colored solution. Therefore, the addition of hydrogen peroxide allows for a colorimetric analysis of the titanium dioxide content (as described below). One of ordinary skill in the art will appreciate that hydrogen peroxide can be replaced with alternative chromogenic reagents, including those known in the art, and will understand how to modify the methods described herein to employ such alternative chromogenic reagents.
[0111] The inventors of the present invention have discovered that the titanium dioxide content of a cellulose acetate sample can be determined by comparing the sample solution with a standard solution having a known concentration of titanium dioxide. The sample solution and the standard solution can be compared by any of a number of indices. In some embodiments, the color of the sample solution is compared to the color of the standard solution. In some of these embodiments, the color of the sample solution can be compared to the color of the standard solution by visual inspection. In some of these embodiments, the color of the sample solution can be compared to the color of the standard solution by using a colorimeter or similar machine. The sample solution and the standard solution can be compared by other indices, such as by spectral analysis, for example, by using a UV-Vis spectrophotometer. In some embodiments, the color of the sample solution can be compared to the color of the standard solution by a combination of these methods.
[0112] In order to accurately determine the titanium dioxide content of cellulose acetate, the method of measuring the titanium dioxide content of cellulose acetate includes titrating a blank solution with a titanium standard. The blank solution preferably contains the same solvent as the sample solution. In some embodiments, for example, the ashed sample is dissolved in water, and the blank solution contains water. In another embodiment, the ashed sample is dissolved in water and sulfuric acid and then treated with hydrogen peroxide, and the blank solution contains water, sulfuric acid, and hydrogen peroxide. In addition, the blank solution preferably contains the same relative amount of solvent as the sample solution.
[0113] The preparation of the titanium standard solution is not particularly limited, and any known method for preparing a titanium dioxide solution of known concentration may be used. According to the method disclosed herein, the titanium standard solution has a known concentration of titanium dioxide. In some embodiments, the titanium standard has a titanium dioxide concentration from 0.1 ppm to 50 ppm, for example, from 0.1 ppm to 40 ppm, from 0.1 ppm to 30 ppm, from 0.1 ppm to 20 ppm, from 0.1 ppm to 10 ppm, from 0.25 ppm to 50 ppm, from 0.25 ppm to 40 ppm, from 0.25 ppm to 30 ppm, from 0.25 ppm to 20 ppm, from 0.25 ppm to 10 ppm, from 0.5 ppm to 50 ppm, from 0.5 ppm to 40 ppm, from 0.5 ppm to 30 ppm, from 0.5 ppm to 20 ppm, from 0.5 ppm to 10 ppm, from 0.75 ppm to 50 ppm, from 0.75 ppm to 40 ppm, from 0.75 ppm to 30 ppm, from 0.75 ppm to 20 ppm, or from 0.75 ppm to 10 ppm. In terms of upper limits, the titanium standard can have a titanium dioxide concentration of less than 50 ppm, for example, less than 40 ppm, less than 30 ppm, less than 20 ppm, or less than 10 ppm. In terms of lower limits, the titanium standard can have a titanium dioxide concentration of greater than 0.1 ppm, for example, greater than 0.25 ppm, greater than 0.5 ppm, or greater than 0.75 ppm.
[0114] There is no particular limitation on the method of titrating the blank solution with the titanium standard, and any known method of titrating the blank solution with a known volume of the titanium standard can be used. As described above, the titrated blank solution is compared with the sample solution by any of various indices, including color and spectral analysis, such as UV-vis, and the blank solution is titrated with the titanium standard until a sufficient volume of the titanium standard is added until a given index (e.g., the color of the titrated blank solution) is consistent with that of the sample solution.
[0115] Because the concentration of titanium dioxide in the titanium standard is known, the amount of titanium dioxide added to the blank solution when the blank solution being titrated is identical to the sample solution can be calculated. From this, the concentration of titanium dioxide in the sample solution, and therefore the concentration of titanium dioxide in the cellulose acetate sample, can be calculated. In embodiments where the cellulose acetate sample is a spinning dope solution of cellulose acetate, the concentration of cellulose acetate in the spinning dope solution is typically required to calculate the concentration of titanium dioxide.
[0116] Measuring the color of cellulose acetate tow
[0117] As described above, previous efforts to produce cellulose acetate tow having a reduced titanium dioxide content (e.g., cellulose acetate tow that is substantially free of titanium dioxide) have been limited due to inadequacies of conventional methods for analytical measurement and / or quality control. In particular, the present inventors have discovered that it is difficult to produce cellulose acetate tow having a low titanium dioxide content of satisfactory quality because certain conventional analytical methods cannot be used for such tow. One example of an analytical method that has limited the development of the cellulose acetate tow described herein is a method for measuring the color of the cellulose acetate tow.
[0118] The color (e.g., whiteness) of cellulose acetate tow is an important feature of its commercial practicality and / or desirability. The importance of the color of cellulose acetate tow is typically considered during the production process of the tow. For example, the production can be designed to produce cellulose acetate tow of a certain color. Similarly, the production can be designed to produce cellulose acetate tow of a consistent color. In order to ensure that these indicators are met, conventional cellulose acetate tow production typically includes measuring the color of the spinning solution solution, which is a good indication of the color of the tow. The color of the spinning solution solution is typically measured using a suitable instrument (e.g., a colorimeter) as "L", "a", and "b" color parameters. The "L" color parameter refers to brightness and typically ranges from 0 (darkest black) to 100 (brightest white). The "a" and "b" color parameters define the axis of color. The "a" color parameter represents the green-red component, where green is negative and red is positive. The "b" color parameter represents blue-yellow, where blue is negative and yellow is positive. The "L" color parameter can be particularly important when measuring the whiteness of cellulose acetate tow products.
[0119] As mentioned above, the pigment titanium dioxide is added to conventional cellulose acetate tow bands. The conventional addition of titanium dioxide ensures color consistency in the spinning dope solution and ultimately in the cellulose acetate tow. In addition, the conventionally added titanium dioxide acts as a matting agent, reducing the brightness of the product tow band.
[0120] The inventors of the present invention have found that the conventional method of measuring the color of spinning solution solution is invalid for measuring the color of spinning solution solution with low titanium dioxide content. When titanium dioxide is not added, the light reflectivity characteristic of spinning solution solution changes. Because the conventional method of measuring the color of spinning solution solution includes the measurement of light, the change of light reflectivity affects color measurement. Therefore, the removal of titanium dioxide makes conventional spectroscopy techniques (e.g., color measurement) invalid.
[0121] As described above, the present disclosure relates to a novel and inventive method for measuring the color of cellulose acetate, which is applicable to cellulose acetate having a low concentration of titanium dioxide. In particular, the method is applicable to measuring the color of cellulose acetate spinning solution. In some embodiments, the method can be used to measure the color of the spinning solution solution before spinning cellulose acetate fibers.
[0122] In some embodiments, the method can be used to measure the color of a dope solution formed by dissolving a sample of cellulose acetate fibers or tow in a suitable solvent. The cellulose acetate tow analyzed by the disclosed method may include cellulose acetate fibers having a denier per filament of less than 12.5. The cellulose acetate tow analyzed by the disclosed method may include cellulose acetate fibers having a denier per filament of greater than 12.5.
[0123] The novel method includes preparing a cake of cellulose acetate from a dope solution; providing a tile; placing the cake and the tile on a reflective port of a colorimeter such that the tile is behind the cake; and recording the color of the cake using the colorimeter.
[0124] The method disclosed herein for measuring the titanium dioxide content of a cellulose acetate spinning solution is applicable to cellulose acetate samples having a relatively low titanium dioxide content. In some embodiments, the method is applicable to cellulose acetate samples having less than 0.1 wt.% (1000 ppm) of titanium dioxide, for example, less than 900 ppm, less than 750 ppm, less than 500 ppm, less than 250 ppm, or less than 100 ppm. In terms of lower limits, the method can be applicable to cellulose acetate samples having a titanium dioxide content greater than 0 ppm, for example, greater than 10 ppm, greater than 15 ppm, or greater than 25 ppm. In terms of ranges, the method can be applied to cellulose acetate samples having a titanium dioxide content of from 0 ppm to 1000 ppm, e.g., from 0 ppm to 900 ppm, from 0 ppm to 750 ppm, from 0 ppm to 500 ppm, from 0 ppm to 250 ppm, from 0 ppm to 100 ppm, from 10 ppm to 1000 ppm, from 10 ppm to 900 ppm, from 10 ppm to 750 ppm, from 1 ...10 ppm to 250 ppm, from 10 ppm to 100ppm, from 15ppm to 1000ppm, for example from 15ppm to 900ppm, from 15ppm to 750ppm, from 15ppm to 500ppm, from 15ppm to 250ppm, from 15ppm to 100ppm, from 25ppm to 1000ppm, for example from 25ppm to 900ppm, from 25ppm to 750ppm, from 25ppm to 500ppm, from 25ppm to 250ppm, or from 25ppm to 100ppm.
[0125] The method for measuring the color of a cellulose acetate spinning solution solution includes preparing a cake of cellulose acetate from the spinning solution solution. The method of forming the cake is not particularly limited, and any known method of forming cellulose acetate from the spinning solution solution into a cake suitable for measurement according to the present method can be used. In some embodiments, the cellulose acetate cake is prepared manually, for example, by pressing by hand. In some embodiments, the cellulose acetate cake is prepared mechanically, for example, by pressing by a press plate or similar machine.
[0126] In some embodiments, the cellulose acetate of the dope solution may be heated before, during, or after pressing. In these embodiments, heating the dope solution makes it easier to evaporate the solvent of the dope solution, which prepares for the formation of a cake of cellulose acetate. In some embodiments, the cake of cellulose acetate is formed by pressing the dope solution on a hot plate. In some embodiments, the dope solution is pressed on a hot plate using a press plate. In embodiments including a hot plate, the hot plate may be at a temperature from 100°C to 200°C, such as from 100°C to 190°C, from 100°C to 180°C, from 100°C to 170°C, from 100°C to 160°C, from 110°C to 200°C, from 110°C to 190°C, from 110°C to 180°C, from 110°C to 170°C, from 110°C to 160°C, from 120°C to 200°C, from 120°C to 1 In some embodiments, the hot plate temperature may be greater than 100° C., for example, greater than 110° C., greater than 120° C., greater than 130° C., or greater than 140° C. In some embodiments, the hot plate temperature may be greater than 200° C., for example, less than 190° C., less than 180° C., less than 170° C., or less than 160° C. In some embodiments, the hot plate temperature may be greater than 100° C., for example, greater than 110° C., greater than 120° C., greater than 130° C., or greater than 140° C. In some embodiments, the hot plate temperature may be less than 200° C., for example, less than 190° C., less than 180° C., less than 170° C., or less than 160° C. In these embodiments, the cellulose acetate tow is preferably allowed to cool.
[0127] The method for measuring the color of a cellulose acetate spinning dope solution includes providing a ceramic sheet and placing a cake and the ceramic sheet on the reflective port of a colorimeter such that the ceramic sheet is behind the cake. As described above, the absence of titanium dioxide in the cellulose acetate spinning dope solution affects the light reflectance properties of cellulose acetate. The inventors of the present invention have discovered that placing the ceramic sheet behind the cake allows accurate measurement of the color of cellulose acetate having a low titanium dioxide content.
[0128] Placing the tile behind the cake of cellulose acetate improves the reflection of light and thereby allows for spectral analysis. The tile used in the method disclosed herein is not particularly limited as long as the tile is suitable for improving reflection. In a preferred embodiment, the tile is substantially white to ensure proper reflection of light. An example of a commercially available tile suitable for use in the method is the BRCA-WT-02C ceramic grayscale tile from Avian Technologies Ltd.
[0129] The method for measuring the color of cellulose acetate includes recording the color of the cake using a colorimeter. The instrument of the colorimeter used in the methods disclosed herein is not particularly limited. An example of a commercially available colorimeter suitable for use in the present method is a HunterLab UltraScan VIS spectrophotometer. The colorimeter is preferably standardized and / or calibrated prior to use.
[0130] After completing a scan of the cellulose acetate cake, the colorimeter preferably reports the color of the cake. Color is typically reported as "L", "a", and "b" values.
[0131] In one embodiment, the cellulose acetate cake has an "L" value from 90 to 100, for example, from 90 to 99.99, from 90 to 99.9, from 90 to 99.5, from 90 to 99, from 91 to 100, from 91 to 99.99, from 91 to 99.9, from 91 to 99.5, from 91 to 99, from 92 to 100, from 92 to 99.99, from 92 to 99.9, from 92 to 99.5, from 92 to 99, from 93 to 100, from 93 to 99.99, from 93 to 99.9, from 93 to 99.5, from 93 to 99, from 94 to 100, from 94 to 99.99, from 94 to 99.9, from 94 to 99.5, or from 94 to 99. In terms of lower limits, the "L" value of the cellulose acetate cake may be greater than 90, e.g., greater than 91, greater than 92, greater than 93, or greater than 94. In terms of upper limits, the "L" value of the cellulose acetate cake may be less than 100, e.g., less than 99.99, less than 99.9, less than 99.5, or less than 99.
[0132] In one embodiment, the cellulose acetate cake has an "a" value from -1 to 0.5, e.g., from -1 to 0.45, from -1 to 0.4, from -1 to 0.35, from -1 to 0.25, from -0.95 to 0.5, from -0.95 to 0.45, from -0.95 to 0.4, from -0.95 to 0.35, from -0.95 to 0.25, from -0.9 to 0.5, from -0.9 to 0.4 5, from -0.9 to 0.4, from -0.9 to 0.35, from -0.9 to 0.25, from -0.85 to 0.5, from -0.85 to 0.45, from -0.85 to 0.4, from -0.85 to 0.35, from -0.85 to 0.25, from -0.8 to 0.5, from -0.8 to 0.45, from -0.8 to 0.4, from -0.8 to 0.35, or from -0.8 to -0.7. In terms of lower limits, the "a" value of the cellulose acetate cake may be greater than -1, for example, greater than -0.95, greater than -0.9, greater than -0.85, or greater than -0.8. In terms of upper limits, the "a" value of the cellulose acetate cake may be less than 0.5, for example, less than 0.45, less than 0.4, less than 0.35, or less than -0.7.
[0133] In one embodiment, the cellulose acetate cake has a "b" value of from 3 to 6, e.g., from 3 to 5.75, from 3 to 5.5, from 3 to 5.25, from 3 to 5, from 3 to 4.75, from 3.25 to 6, from 3.25 to 5.75, from 3.25 to 5.5, from 3.25 to 5.25, from 3.25 to 5, from 3.25 to 4.75, from 3.5 to 6, from 3.5 to 5.75, from 3.5 to 5.5, from 3.5 to 5.25, from 3.5 to 5, From 3.5 to 4.75, from 3.75 to 6, from 3.75 to 5.75, from 3.75 to 5.5, from 3.75 to 5.25, from 3.75 to 5, from 3.75 to 4.75, from 4 to 6, from 4 to 5.75, from 4 to 5.5, from 4 to 5.25, from 4 to 5, from 4 to 4.75, from 4.25 to 6, from 4.25 to 5.75, from 4.25 to 5.5, from 4.25 to 5.25, from 4.25 to 5, or from 4.25 to 4.75. In terms of lower limits, the "b" value of the cellulose cake can be greater than 3, for example, greater than 3.25, greater than 3.5, greater than 3.75, greater than 4, or greater than 4.25. In terms of upper limits, the "b" value of the cellulose acetate cake can be less than 6, eg, less than 5.75, less than 5.5, less than 5.25, less than 5, or less than 4.75.
[0134] Although the present invention has been described in detail, modifications within the spirit and scope of the present invention will be apparent to those skilled in the art. It should be understood that the various aspects of the present invention and the various embodiments and portions of the various features described above and / or in the appended claims may be combined or interchanged in whole or in part. In the above description of the various embodiments, those embodiments that mention another embodiment may be appropriately combined with other embodiments, as understood by those of ordinary skill in the art. In addition, it will be understood by those of ordinary skill in the art that the above description is by way of example only and is not intended to limit the present invention. All U.S. patents and publications cited herein are incorporated by reference in their entirety.
[0135] Examples
[0136] Example 1
[0137] The disclosed method for measuring titanium dioxide was used to measure titanium dioxide on several samples of cellulose acetate tow.
[0138] Each tow sample was prepared by treating with isopropanol. Specifically, each tow sample was shaken in the presence of isopropanol in a wrist shaker. The tow sample was then squeezed to remove excess isopropanol, placed in a fume hood to dry, and then placed in an oven to dry.
[0139] Each tow sample was then ashed by burning with a Bunsen burner until the sample burned out and then placed in a muffle furnace for one hour or until the sample was completely ashed and no glowing particles remained.
[0140] After ashing, each tow sample was allowed to cool. The sample was then treated with potassium bisulfate and burned again until all solid material was liquefied. The liquefied ashed sample was then dissolved in sulfuric acid and treated with hydrogen peroxide.
[0141] The titanium dioxide content of each tow sample was determined by titrating a blank solution with a titanium standard. The blank solution contained water, sulfuric acid, and hydrogen peroxide. The titanium standard contained 0.1 ppm of titanium dioxide. The titanium standard was added to the blank solution until the color of the blank solution matched the color of each sample. The titanium dioxide content of the tow sample was calculated using the volume of titanium standard added to the blank solution. The results for several samples are reported in Table 1 below:
[0142] Table 1
[0143]
[0144] Example 2
[0145] The disclosed method for measuring titanium dioxide was used to measure titanium dioxide of several samples of cellulose acetate spinning solution. Each spinning solution sample contained a solution of cellulose acetate and a mixture of water and acetone as a solvent. Each sample had a spinning solution solid concentration ranging from 20 wt.% to 35 wt.%.
[0146] Each dope sample was ashed by burning with a Bunsen burner until the sample burned out and then placed in a muffle furnace for one hour or until the sample was completely ashed and no glowing particles remained.
[0147] After ashing, each dope sample was allowed to cool. The sample was then treated with potassium bisulfate and burned again until all solid material was liquefied. The liquefied ashed sample was then dissolved in sulfuric acid and treated with hydrogen peroxide.
[0148] The titanium dioxide content of each spinning solution sample was determined by titrating a blank solution with a titanium standard. The blank solution contained water, sulfuric acid, and hydrogen peroxide. The titanium standard contained 0.1 ppm of titanium dioxide. The titanium standard was added to the blank solution until the color of the blank solution was consistent with the color of each sample. The titanium dioxide content of the spinning solution sample was calculated using the volume of the titanium standard added to the blank solution. The results of several samples are reported in Table 2 below:
[0149] Table 2
[0150]
[0151]
[0152] Example 3
[0153] The disclosed method for measuring titanium dioxide was used to measure the color of several samples of cellulose acetate spinning solution. Each spinning solution sample contained a solution of cellulose acetate and a mixture of water and acetone as a solvent.
[0154] A cake of cellulose acetate was prepared from each dope sample. Specifically, each cake was prepared by pressing about 4 to 5 grams of each dope sample on a hot plate using a press plate. The hot plate was set to about 150° C. Each sample was covered on the hot plate for about 5 minutes, after which the cake was removed and allowed to cool.
[0155] The color of each cake was measured using a colorimeter, specifically a HunterLab UltraScan VIS spectrophotometer. Each cake was placed on the reflective port of the colorimeter with the white tile behind the cake. The colorimeter then recorded the color of each cake and reported the color as "L", "a", and "b" values. The results for several samples are reported in Table 3 below:
[0156] Table 3
[0157]
Claims
1. A tow belt comprising Cellulose acetate fibers having a denier per filament of less than 12.5; wherein the tow band comprises less than 0.1 wt.% titanium dioxide as measured by ashing and titration and / or by titanium particle count density; And wherein the filament band has an "L" value from 90 to 100 measured from a spinning dope solution, an "a" value from -1 to 0.5, and a "b" value from 3 to 6, wherein the "L" color parameter refers to brightness, and the "a" and "b" color parameters define the axis of color; the "a" color parameter represents a green-red component, wherein green is a negative value and red is a positive value, and the "b" color parameter represents a blue-yellow component, wherein blue is a negative value and yellow is a positive value.
2. The tow band of claim 1 comprising less than 0.01 wt.% titanium dioxide.
3. The tow belt according to claim 1 or 2, wherein: The tow band has an ash weight of less than 0.1% of the tow band.
4. The tow belt according to claim 1 or 2, wherein: The tow band has less than 1.0 titanium dioxide particles per denier.
5. The tow belt according to claim 1 or 2, wherein: The tow band has a total denier of from 5,000 to 100,000.
6. The tow belt according to claim 1 or 2, wherein: The cellulose acetate fibers have a cross-sectional shape selected from the group consisting of circular, crenulated, oval, polygonal, dog-bone, "Y", "X", "K", "C", and multi-lobal.
7. A method for measuring the titanium dioxide content of cellulose acetate in the tow band of claim 1, the method comprising: preparing a sample of cellulose acetate for measurement; ashing the sample to form an ashed sample; dissolving the ashed sample to form a sample solution; Titrate the blank solution with the titanium standard; as well as The titrated blank solution was compared to the sample solution.
8. The method of claim 7, wherein: The cellulose acetate has a titanium dioxide content of less than 1000 ppm.
9. The method according to claim 7 or 8, wherein: The preparation includes treating the cellulose acetate with an organic non-solvent selected from the group consisting of alcohols, ethers, ketones and esters.
10. The tow belt according to claim 9, wherein: The organic non-solvent is selected from the group consisting of isopropyl alcohol, diethyl ether, 2-butanol, methyl tert-butyl ether, isopropyl ether, 2-pentanone, isobutyl acetate and ethylene glycol methyl ether.
11. The method according to claim 7 or 8, wherein: The ashing further comprises: combusting the sample; and Treating with a salt selected from the group consisting of sodium pyrosulfate, sodium sulfate, sodium bisulfate, potassium pyrosulfate, potassium bisulfate, potassium sulfate, and potassium bisulfate.
12. The method according to claim 7 or 8, wherein: The dissolving includes dissolving the ashed sample in water and / or acid.
13. The method of claim 7 or 8, further comprising treating the sample solution with hydrogen peroxide.
14. The method according to claim 7 or 8, wherein: The blank solution contained water, sulfuric acid and hydrogen peroxide.
15. The method according to claim 7 or 8, wherein: The titanium standard contains from 0.1 to 50 ppm titanium dioxide.
16. A method for measuring the color of a dope solution of cellulose acetate in the tow band of claim 1, the method comprising: preparing a cellulose acetate cake from the spinning dope solution; Provide tiles; placing the cake and the tile on the reflection port of the colorimeter so that the tile is behind the cake; as well as The color of the cake was recorded using the colorimeter.
17. The method of claim 16, wherein: The preparation involves pressing the cellulose acetate on a hot plate.
18. The method according to claim 16 or 17, wherein: The tile is white.
19. A tow belt comprising: Cellulose acetate fibers having a single filament denier of less than 12.5 and a total denier of from 5,000 to 100,000; wherein the filamentary band is substantially free of titanium dioxide; and wherein the tow band has an "L" value from 90 to 100, an "a" value from -1 to 0.5, and a "b" value from 3 to 6 as measured from a spinning dope solution; Where the "L" color parameter refers to brightness, the "a" and "b" color parameters define the axis of color; the "a" color parameter represents the green-red component, where green is negative and red is positive, and the "b" color parameter represents the blue-yellow component, where blue is negative and yellow is positive.
20. A tow belt comprising: Cellulose acetate fibers having a denier per filament of less than 12.5; wherein the filamentary band contains less than 0.1 wt.% titanium dioxide, wherein the filamentary band has an average titanium dioxide particle density of less than 1.0 titanium dioxide particle / fiber denier; and wherein the tow band has an "L" value from 90 to 100, an "a" value from -1 to 0.5, and a "b" value from 3 to 6 as measured from a spinning dope solution; Where the "L" color parameter refers to brightness, the "a" and "b" color parameters define the axis of color; the "a" color parameter represents the green-red component, where green is negative and red is positive, and the "b" color parameter represents the blue-yellow component, where blue is negative and yellow is positive.
21. The tow belt according to claim 20, wherein: The tow band has a total denier greater than 20,000.
Citation Information
Patent Citations
Methods for Synthesizing Acylated Cellulose Through Instillation of an Acidic Catalyst
US20130096297A1
High Denier Per Filament and Low Total Denier Tow Bands
US20130115452A1
Products of high denier per filament and low total denier tow bands
US20150128964A1
Process for the preparation of riboflavin-5'-monophosphoric acid ester
US2740775A
Process of making cellulose acetate tow
US7585441B2